Awareness of Oral Cancer in a Community of Tarahara, Sunsari, Nepal - Rai, Poonam; Mandal, Punam Kumari; Yangden, Namita; Rai, Munawatee; Subedi, Sabitra (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Oral cancer is one of the highly prevalent cancers worldwide and a leading cause of mortality in certain regions like South-Central Asia and a major public health problem. According to National Health Policy, oral cancer is the most common form of cancer in men and the third most common cancer in females in Nepal. Several studies have shown that public is not well aware of risk factors associated with oral cancer. The objective of this study was to assess the awareness of oral cancer among people of Tarahara-20. Material and Methods: A cross-sectional descriptive study was conducted among people of age group 18-65 years in 2019. Data were collected from 128 respondents through face to face interview using Semi – structured interview schedule with non-probability purposive sampling method. Data entry and analysis was done in SPSS version 17. Descriptive statistics i.e. frequency, percentage, mean and standard deviation was used to assess the level of knowledge and inferential statistics i.e. chi square was used to find the association between awareness of oral cancer and selected demographic variables. Results: Total findings of the study showed that More than half (52.3%) of respondents were known about treatment modalities of Oral cancer whereas two third, 78.9% of respondents stated out movement is best for physical rehabilitation. Likewise, more than half (65.6%) had moderate level of awareness and 28.1% of the respondents had inadequate level of awareness regarding oral cancer. The result showed there was no association between level of awareness of oral cancer and selected demographic variables. Conclusion: The study concluded that awareness regarding oral cancer is moderate among community people of Tarhara. It reflects that efforts should be made to increase the awareness regarding oral cancer. Health education regarding oral cancer and its risk factors with periodic reinforcement will play an important role in creating awareness.